Immunological markers and clinical outcome of advanced melanoma patients receiving ipilimumab plus fotemustine in the NIBIT-M1 study. (1st February 2016) - Maccalli, Cristina; Giannarelli, Diana; Capocefalo, Filippo; Pilla, Lorenzo; Fonsatti, Ester; Di Giacomo, Anna Maria; Parmiani, Giorgio; Maio, Michele
ABSTRACT: Clinical activity was observed in metastatic melanoma (MM) patients treated with ipilimumab (IPI) combined with fotemustine (FTM) in the phase II NIBIT-M1 study. Peripheral blood mononuclear cells (PBMCs) and serum were collected from MM patients at pre- and at weeks 12 and 24 post-treatment. A comprehensive phenotypic and functional immunomonitoring of circulating T cells, and the detection of soluble immunoregulatory molecules was carried out and correlated with clinical outcome. The frequency at baseline and along the treatment of circulating T central memory cells expressing activation/differentiation markers, such as CD3 + CD4 + CD45RO + BTLA +, CD3 + CD4 + 4–1BB or Th17 lymphocytes correlated with the clinical outcome of MM patients. Moreover, either the absence or the presence of soluble NKG2D ligands (ULBP-1 or −2) at baseline in the serum of MM patients enabled to discriminate subjects with long-term survival (median overall survival, (OS) = 33.6 mo for ULBP-1 and −2) from poor survivors (OS = 9.8 or 6.6 mo, respectively). Conversely, no significant association between the levels of soluble MICA, MICB and ULBP-3 and the clinical outcome of patients was observed. An inverse correlation between circulating levels of these molecules at baseline and frequency of either CD3 + CD4 + CD45RO + BTLA + or Th17 or CD3 + CD4 + 4–1BB + T cells occurred in patients with a favorable clinical outcome. The simultaneous monitoring of different immune parameters, though validation in a large cohort of patients is needed, allowed to identify an association between phenotypic and soluble markers representing a possible predictive immunological signature for the clinical activity of IPI plus FTM.